2007
DOI: 10.1111/j.1365-2710.2007.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of quinine and its metabolites in pregnant Sudanese women with uncomplicated Plasmodium falciparum malaria

Abstract: There was no significant difference in quinine metabolism between pregnant and non-pregnant women and there is no need to adjust quinine dose when treating pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…In the case of propranolol, mean elimination half-life in pregnancy was shorter in both studies, but the exposure parameter (AUC) changes were not consistent; non-significant increase in the AUC [218] versus non-significant decrease in AUC [219]. Consistent but non-significant increase in Cl was reported for quinine [189,220222]. Plasma folate concentrations showed no statistically significant changes [221,222], but conflicting change directions were seen in the mean values, depending on the dose [222].…”
Section: Resultsmentioning
confidence: 86%
“…In the case of propranolol, mean elimination half-life in pregnancy was shorter in both studies, but the exposure parameter (AUC) changes were not consistent; non-significant increase in the AUC [218] versus non-significant decrease in AUC [219]. Consistent but non-significant increase in Cl was reported for quinine [189,220222]. Plasma folate concentrations showed no statistically significant changes [221,222], but conflicting change directions were seen in the mean values, depending on the dose [222].…”
Section: Resultsmentioning
confidence: 86%
“…Quantification was performed using selected reaction monitoring (SRM) for the transitions m/z 356 -283 and 328 -283 for amodiaquine and desethylamodiaquine, respectively, and 336 -247 for the internal standard hydroxychloroquine. Total assay coefficients of variation (CV) for amodiaquine and desethylamodiaquine during analysis were less than 15% at all quality control levels (1,5,8,25, and 80 ng/ml for amodiaquine and 2, 10, 16, 50, and 400 ng/ml for desethylamodiaquine). The lower limit of quantification (LLOQ) was set to 1 ng/ml and 2 ng/ml for amodiaquine and desethylamodiaquine, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A noncompartmental analysis of amodiaquine and desethylamodiaquine reported no significant pharmacokinetic difference in pregnant women and postpartum women (48). Studies in pregnant women with malaria reported relatively unchanged pharmacokinetic properties of chloroquine and quinine (1,27). However, a recent publication reported significantly lower exposure of both chloroquine and its active metabolite, desethylchloroquine, when administered as intermittent presumptive treatment in pregnancy for malaria (24).…”
mentioning
confidence: 97%
“…Whereas blood chloroquine and quinine concentrations are relatively unaffected (1,25), artesunate, artemether, dihydroartemisinin, sulfadoxine, atovaquone, proguanil, and cycloguanil concentrations are all reduced in later pregnancy (14,(30)(31)(32)(33). The reductions are often substantial, and as a result, antimalarial cure rates in pregnancy for any given antimalarial drug tend to be lower (24,34).…”
mentioning
confidence: 99%